Scientific Publishing Differences between Sexes in Cardiology, Cardiac, and General Surgery - Färber, Gloria; Alscher, Leonhard; Heyne, Estelle; Doenst, Torsten; Schwarzer, Michael (The Thoracic and Cardiovascular Surgeon, 2021)
Background Research and scientific publications are important for the advancement of science but also for the individual career development. While women have become the majority of students in medicine we do not know about female presence and scientific activity in cardiac surgery. We thus aimed to compare scientific output of women and men in German University departments of cardiac surgery with cardiology departments focusing on the same organ and surgical departments not addressing the heart (general surgery) of 34 universities in Germany.Methods Personnel working at University departments was identified on the institutions internet homepage in 2014. Publications in 2011 to 2013 on PubMed were identified. Author and manuscript characteristics were determined.Results A lower proportion of women were working in cardiac surgery (25%) compared with cardiology (35%) and general (32%) surgery independent of executive function or academic degree. Scientifically active women published fewer manuscripts per capita than men both, in total and as first author. Additionally, the mean and the cumulated journal impact factor of the journals chosen was lower for women compared with men in cardiology but not in cardiac and general surgery.Conclusion We conclude that the differences in scientific activity between women and men are more pronounced in cardiology compared with general and cardiac surgery, indicating that a higher proportion of women in a field does not result in reduced differences between sexes. The low number of women together with the lower number of manuscripts in cardiac surgery may render the appointment of women as directors challenging.
Keywords: cardiac surgery departments; PubMed database; scientific output; sex differences